Decree No. 108 of the year 2016 Promulgating the Executive Regulations Of the Law Regulating Movable Guarantees As Promulgated by Law No. 115 of the year 2015 قرار رقم 108 لسنة 2016 بإصدار اللائحة التنفيذية لقانون تنظيم الضمانات المنقولة الصادر بالقانون رقم 115 لسنة 2015 - Egypt; The middle east library for economic services, translator. (2025)
Law no. 108 of the year 2016 promulgated the executive regulations of the law regulating movable guarantees -- chapter 1: definitions – chapter 2: scope of application – chapter 3: movable guarantee registry – chapter 4: rules for registering certain security interests in registry – chapter 5: rules for registering certain security interests – chapter 6: registering security interests created over movable assets before enforcement of this law -- Chapter 7: registering security fees – chapter 8: provisions governing security interests and priority – chapter 9: provisions governing execution against collaterals القرار رقم 108 لسنة 2016 بإصدار اللائحة التنفيذية لقانون تنظيم الضمانات المقولة الصادر بالقانون رقم 115 لسنة 2015 – الفصل الأول التعريفات – الفصل الثانى نطلق التطبيق – الفصل الثالث سجل الضمانات المنقولة – الفصل الرابع قواعد شهر حقوق الضمان بالسجل – الفصل الخامس أحكام خاصة بإشهار بعض حقوق الضمان – الفصل السادس إشهار الحقوق المنشأة على المنقولات قبل نفاذ هذا القانون – الفصل السابع مقابل خدمات الإشهار بالسجل – الفصل الثامن الأحكام المتعلقة بحقوق الضمان والأولوية – الفصل التاسع الأحكام المتعلقة بالتنفيذ على المنقول الضامن